2020
DOI: 10.1038/s41388-020-01388-8
|View full text |Cite|
|
Sign up to set email alerts
|

AR-induced long non-coding RNA LINC01503 facilitates proliferation and metastasis via the SFPQ-FOSL1 axis in nasopharyngeal carcinoma

Abstract: Increasing evidence indicates that long non-coding RNAs (lncRNAs) play vital roles in the tumorigenesis and progression of cancers. However, the functions and regulatory mechanisms of lncRNAs in nasopharyngeal carcinoma (NPC) are still largely unknown. Our previous lncRNA expression profiles identified that LINC01503 was overexpressed in NPC. Here, we verified that LINC01503 was highly expressed in NPC and correlated with poor prognosis. LINC01503 promoted NPC cell proliferation, migration, and invasion in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…And the results proved that our findings are accurate and reliable. For example, LINC01503 was confirmed to be correlated with the OS of CRC patients, and other studies have also found that it is highly expressed in different tumor cells, and is positively correlated with tumor cell proliferation and metastasis, including nasopharyngeal carcinoma ( He et al, 2020 ), gastric cancer ( Ding et al, 2020 ; Ma et al, 2020 ), and CRC ( Wei et al, 2020 ). Interestingly, in cholangiocarcinoma, LINC01503 can also promote the EMT process ( Qu et al, 2019 ), confirming that this lncRNA is an EMT-related lncRNA.…”
Section: Discussionmentioning
confidence: 81%
“…And the results proved that our findings are accurate and reliable. For example, LINC01503 was confirmed to be correlated with the OS of CRC patients, and other studies have also found that it is highly expressed in different tumor cells, and is positively correlated with tumor cell proliferation and metastasis, including nasopharyngeal carcinoma ( He et al, 2020 ), gastric cancer ( Ding et al, 2020 ; Ma et al, 2020 ), and CRC ( Wei et al, 2020 ). Interestingly, in cholangiocarcinoma, LINC01503 can also promote the EMT process ( Qu et al, 2019 ), confirming that this lncRNA is an EMT-related lncRNA.…”
Section: Discussionmentioning
confidence: 81%
“…As demonstrated by accumulated evidence, LINC01503 aggravates the progression of several malignancies, such as nasopharyngeal carcinoma [ 31 ], cholangiocarcinoma [ 32 ], and hepatocellular carcinoma [ 33 ]. According to an investigation performed with TCGA, LINC01503 was highly expressed in OV tissues, compared with corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA FAM225A acts as ceRNA to sponge miR-590-3p/miR-1275 and upregulates ITGB3 to promote NPC metastasis [114]. Long non-coding RNA LINC01503 stimulates NPC metastasis by recruiting splicing factor proline-and glutamine-rich (SFPQ) to activate Fos-like 1 (FOSL1) transcription [115]. MicroRNA-494-3p promotes NPC cellular motility and growth by targeting Sox7 [116].…”
Section: Non-coding Rnasmentioning
confidence: 99%